Uji Organoleptik dan Daya Terima Produk Sari Kacang Hijau Kencur sebagai Pangan Fungsional - Rahmadiana, Wahyu; Farapti, Farapti (Media Gizi Kesmas, 2024)
Background: Mung beans contain vitamin B6, vitamin C and vitamin E that function to regulate reproductive hormones to the maximum and natural antioxidants that counter free radicals. Kencur is one of the herbal plants that grows fertile in mountainous areas and is often used as a cure, including cough, nausea, swelling, bruising, diarrhea and antitoxins. In 2017, the total production of kencur in Indonesia reached 36,655 tons. Innovation and creation are needed in processing the combination of these two food ingredients to increase the sales value because of the abundance of the production of mung beans and kencur in Indonesia. The development of processed products of mung beans and kencur is expected to be accepted by the general public because of its health benefits. Objectives: This study aims to find out the acceptance of extract kencur mung bean products and the benefit of mung bean and kencur as healthy foods that are acceptable to consumers. Methods: The design used in this study was a trial or experiment research. The research was carried out on 5 trained panels and 30 untrained panels who would perform organoleptic tests on one product, namely, extract kencur mung beans. Results: According to the organoleptic test results on extract kencur mung bean, the panelists liked the taste, color, smells and texture indicators. It can be seen from the test results on the indicators of taste, color, smells, and texture that the panelist likes the preferred category. Whereas in the acceptance test using the hedonic test, the results obtained were, 10 out of 35 panelists chose very like it and 19 out of 35 panelists chose to like the product extract kencur mung bean. Conclusion: Mung beans are acceptable and preferred by consumers in terms of taste, colour, smells, and texture.